An exploratory study of urinary proteome in trigeminal neuralgia - Wei, Lilong; Wang, Haitong; Zhou, Yun; Wu, Jianqiang; Cao, Yongtong; Zhan, Yuliang; Gao, Youhe (Frontiers in Molecular Biosciences, 2025)
BackgroundTrigeminal neuralgia (TN) is a neurological disorder characterized by severe pain and a complex pathogenesis. This condition seriously affects patients’ quality of life. The analysis of urinary proteomics has shown great potential in disease research.ObjectiveThe aim of this study is to explore the diagnostic and therapeutic value of urine proteomics in TN.MethodThe urine of 10 cases of TN and 11 healthy individuals were studied using liquid chromatography-mass spectrometry (LC-MS) proteomics technology. Group analysis and one to many individual analysis strategies were used in quantitative analysis.ResultA total of 2,620 proteins were identified in the group analysis, and 1,883 of them were quantifiable. Most specimens in each group were distinguishable through clustering analysis of the urinary proteome. Significant enrichment was observed in biological processes such as immune response-regulating signaling pathway, regulation of complement activation, natural killer cell inhibitory signaling pathway, and cytoplasmic translation, as well as in KEGG pathways including antigen processing and presentation, and complement and coagulation cascades. Individual analysis revealed a higher number of significantly different proteins between patients, with seven proteins identified in at least nine patients.ConclusionThe urinary proteome provided molecular characteristics of urinary proteins in patients. It described the changes that occur in the patient’s body. The strong enrichment of immune response pathways may be linked to disease onset, suggesting new avenues for immune-based treatments, and the significant differential proteins could become potential disease markers for diagnosis and treatment evaluation.